Rheology of Fluid and Semisolid Foods: Principles and Applications - Rao, M. A. Andy (Food Engineering Series, 2007)
The second edition of Rheology of Fluid and Semisolid Foods: Principles and Application, examines the concepts needed to characterize rheological behavior of fluid and semisolid foods and to use various ingredients to develop desirable flow properties in fluid foods, and structure in gelled systems. It covers important applications of rheology to sensory assessment and swallowing, and handling and processing foods. All of the chapters have been updated to help readers better understand the importance rheological properties play in food science and utilize these properties to characterize food. About the Author: M. A. "Andy" Rao is a Professor Emeritus of Food Engineering, Cornell University. He received the Scott Blair Award for Excellence in Rheology of American Association of Cereal Chemists), the Distinguished Food Engineering Award of American Society of Agricultural Engineers, and elected a Fellow of the Institute of Food Technologists. Dr. Rao helped develop the "Vane Method" measurement of yield stress for a variety of food products -- a standard measurement tool used by the food industry today. He has actively supported and promoted food engineering through cooperative professional teaching and research activities in Brazil, India, Mexico, New Zealand, Portugal, and Thailand.